Manuscript copy of poem 'The Poddle's flowery banks : in imitation of a street ballad' by P.J. McCall - McCall, Patrick Joseph, 1861-1919; O'Brennan, Lily M., 1878-1948 (1938)
With a short cover note in an unknown hand, introducing the poem and sending good wishes to Lily O'Brennan and family while wishing her luck [at her presentation of the lecture 'Little rivers of Dublin'] on Monday.
Inscribed on 'Westpoint House, Strand Road, Sutton, Co. Dublin' headed paper.
Keywords: O'Brennan, Kathleen M., -- 1876-1948; Rivers -- Ireland -- Dublin; Rivers -- Ireland -- Dublin (County); Ireland -- History -- 1922-